2020
DOI: 10.1007/s00167-020-06125-y
|View full text |Cite
|
Sign up to set email alerts
|

Remnant preservation does not affect accuracy of tibial tunnel positioning in single-bundle ACL reconstruction

Abstract: Purpose Remnant preservation, in anterior cruciate ligament (ACL) reconstruction, has potential biological advantages. However, graft positioning remains vital to functional outcome and the prevention of failure. The aim of this study was to investigate the accuracy and precision of tibial tunnel positioning in remnant preservation single-bundle hamstring reconstruction.Methods Fifty consecutive adult patients, with isolated ACL rupture, were recruited to a prospective study. Remnant preservation was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 30 publications
(52 reference statements)
1
25
0
Order By: Relevance
“…The surgeon has to consider numerous factors whilst operating within the anatomic boundaries of the femoral intercondylar notch and tibial eminences. Of these factors, tunnel positioning is most essential to achieve an anatomic graft position and an excellent ACL reconstruction [ 2 , 3 , 9 , 20 , 21 , 23 , 24 , 28 , 36 , 40 , 41 , 43 , 46 , 51 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…The surgeon has to consider numerous factors whilst operating within the anatomic boundaries of the femoral intercondylar notch and tibial eminences. Of these factors, tunnel positioning is most essential to achieve an anatomic graft position and an excellent ACL reconstruction [ 2 , 3 , 9 , 20 , 21 , 23 , 24 , 28 , 36 , 40 , 41 , 43 , 46 , 51 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…The average IKDC was 88.7 ± 14.1, and the average Lysholm score was 89.4 ± 12.3, with a minimum follow-up of two years. Unlike for the anterior cruciate ligament (ACL), the extant literature on the posterior cruciate ligament (PCL) does not demonstrate the superiority of these techniques compared to conventional techniques [9,12,23], due to a lack of prospective, randomised studies, making it hard to decide whether preserving the remnant is advantageous or not. Nevertheless, some authors have described favourable results (IKDC rating of A or B in 97% to 100%) after chronic PCLR (> 6 months) ( [1].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Kosy et al, 20 the authors evaluated the accuracy and precision of the tibial tunnel in the RP and RA groups using the mean AP (38.7%) and ML (49.1%) positions determined by Lertwanich et al 21 as the reference standard. Those authors reported no significant differences between groups regarding these metrics, and their work is therefore broadly consistent with the findings of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors reported no significant differences between groups regarding these metrics, and their work is therefore broadly consistent with the findings of the current study. However, in light of the reported variation in the center of the anatomic footprint when correlated with 3D-CT, it is unsurprising that Kosy et al 20 reported accuracies between 4.8% and 6.1% and a precision between 2.8% and 3.9% when using a specific point as a reference standard. It could perhaps be argued that these metrics are incorrectly used because none of the intraoperative steps taken or landmarks used actually sought to achieve this specific position that was identified only on postoperative CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation